Serial Mediated Effects of Memorable Tourism Experience and Place Attachment in Transmitting Experience Economy to Tourism Loyalty in the Eastern Lanna Special Economic Area - Srivirach, Jeeradech; Narakorn, Prasittichai; Seesupan, Tummatinna (Rajapark Journal, 2024)
The objectives of this research were to study the relationship between experience economy, memorable tourism experience, place attachment, and tourism loyalty. This is quantitative research using multi-stage sampling from a group of 552 tourists who have visited the Eastern Lanna Special Economic Zone. The model was analyzed using structural equation modeling (SEM). The proposed model was tested using structural equation modeling (SEM). The results showed that our data explained the model very well, whereby tourism loyalty was driven by experience economy, memorable tourism experience, and place attachment. The findings could help SME entrepreneurs understand the importance of memorable tourism experiences, which directly influence tourism loyalty. Particularly, those SME entrepreneurs with place attachments should emphasize the tourists’ impressions for visits again. The study proposed model was conceptualized using experience economy theory together with memorable tourism experience theory, aiming at enhancing the competitiveness of SME entrepreneurs in the Eastern Lanna Special Economic Area.